Transport of melt, pressure and heat through a magma mush - Liao, Yang (Frontiers in Earth Science, 2023)
Prior to intrusion, magma migrates through the crustal plumbing system that likely contains layers or columns of crystal mush. To better understand the behavior of the crustal magmatic system during magmatic unrest, it is important to examine the process of melt migration within the crystal mush and the associated evolution in pressure and temperature. In this study I use an analytical model to explore the characteristics of transport of melt, pressure, and heat through an idealized crystal mush layer/column under uniaxial strain condition. The model invokes a thermo-poro-viscoelastic rheology and uses a frequency-domain method to explore two scenarios of magmatic unrest: harmonic perturbation of fluid pressure, and step-rise in fluid pressure at a source location. Several factors influence the transport of melt, pressure and heat, including the thermal-mechanical coupling arising from the mush rheology, the advection of heat by melt flows, the competition between thermal diffusivity and poroelastic diffusivity, and the viscoelastic relaxation of the crystalline framework. One key finding is the development of transport asymmetry: when a background temperature gradient exists, the transport properties become different for propagation along the background thermal gradient and propagation against the background thermal gradient. Analysis on an endmember case shows that the transport asymmetry is associated to the competition between the diffusion and advection of pore pressure, which determines a Peclet number that depends on the temperature difference across the mush and the thermal expansion coefficients. Because the temperature in magma mushes in the crust likely increase with depth, the observed propagation asymmetry suggests some intrinsic difference between a bottom-up vs. a top-down triggering mechanism for magmatic unrest. The results from this study highlight the importance for further exploration for a more complete description of the transport properties in the crystal mush.